Feeling is Movement - Pashman, Susan 1942- (Edinburgh: Edinburgh University Press, 2017)
RESUMEN: This article deals with Antonio Damasio's significant contribution to clarifying the precise way expression works in dance. Damasio's neural model of consciousness, I believe, supplies the precision of terminology that allows aestheticians to link an observed object, the artwork, to the emotional experience of observing it. Damasio's "double" notion of kinaesthesia provides a clear and useful way of distinguishing the neural aspects of the aesthetic experience from those best left to phenomenology. PALABRAS CLAVE: Kinaesthesia, Damasio, movement, emotion, expression